Cancer stem cells versus phenotype-switching in melanoma - Hoek, Keith S.; Goding, Colin R. (Pigment cell and melanoma research, 2010)
Summary Tumours comprise multiple phenotypically distinct subpopulations of cells, some of which are proposed to possess stem cell‐like properties, being able to self‐renew, seed and maintain tumours, and provide a reservoir of therapeutically resistant cells. Here, we use melanoma as a model to explore the validity of the cancer stem cell hypothesis in the light of accumulating evidence that melanoma progression may instead be driven by phenotype‐switching triggered by genetic lesions that impose an increased sensitivity to changes in the tumour microenvironment. Although at any given moment cells within a tumour may exhibit differentiated, proliferative or invasive phenotypes, an ability to switch phenotypes implies that most cells will have the potential to adopt a stem cell‐like identity. Insights into the molecular events underpinning phenotype‐switching in melanoma highlight the close relationship between signalling pathways that generate, maintain and activate melanocyte stem cells as well as the inverse correlation between proliferation and invasive potentials. An understanding of phenotype‐switching in melanoma, and in particular the signalling events that regulate the expression of the microphthalmia‐associated transcription factor Mitf, points to new therapeutic opportunities aimed at eradicating therapeutically resistant stem cell‐like melanoma cells.